Visual Acuity Estimation using Stepwise Sweep Visual Evoked Potentials in Normal Participants and Patients with Optic Neuropathy and Age-Related Macular Degeneration - Hermas, Asma (Université d'Ottawa / University of Ottawa, 2025)
Statement of the Problem: This thesis investigates how effective sweep visual evoked potentials are in determining visual acuity compared to the Snellen chart in patients with optic neuropathy and age-related macular degeneration. The study will determine how the parameters of sVEP can affect its ability to estimate visual acuity and how sVEP can correlate with foveal threshold (FT), ganglion cell layer (GCL) thickness, and distance from the inner limiting membrane to the retinal pigment epithelium (ILM-RPE) in these diseases. Methodology: The present research adopts a comparative approach that uses a combination of methods involving both traditional visual acuity tests and electrophysiological measures. The sVEP data were analyzed along with structural imaging, and a functional assessment of the retina was done to assess the correlation between sVEP results, GCL thickness, foveal threshold, and ILM-RPE in patients with ON and AMD. Main Findings: The results show that using sVEP cannot substitute for the Snellen chart for ON and AMD patients; however, it is suitable for patients for whom the Snellen chart is not suitable and challenging to perform. It was observed that the sVEP had a significant correlation with certain functional changes in the retina and may provide insights into the pathophysiology of the visual impairment in ON and AMD. Conclusion: Using sVEP as an assessment tool for visual function was most helpful to supplement conventional visual acuity tests in complex cases. The findings reinforce the potential of sVEP to make available better and enhanced knowledge regarding visual processing in relation to retinal diseases and to be widely applied in the clinic and for research purposes to better assess visual function and disease progression.